Children monitoring system using radio frequency (RF) technology - Nurul Izzah, Ishak (2012)
Children Monitoring System (CMS)is a prototype device which is developed to represent how the original idea proposed which is a pair of device that are designed for children and parents where it can reduce the anxiety of the parents will lose their children while shopping at the mall.It also ensures security to prevent the disappearance of the child when in public places.This is because this product is based on the situation in which the loss occurred when the children are shopping or while in a lot of people. Technology used for this prototype is Radio Frequency(RF). According to Alina et al.(2010),radio frequency refers to alternating current (AC) which hold element such that,if the current is input to an antenna,an electromagnetic(EM) field is produce appropriate for wireless broadcasting and communications.Privileges available to product are the device that represent as children may issue loss of signal when it is reach the limitation distance which is 1.5m for this prototype project. While the device that represent as the mother or father also may emit a sound signal beep and display that “kids are missing” at the LCD when it is reach the limitation distance.Currently,parents will know where their children and continue to get their children and aware from any missing occur.